Relationship of the obturator nerve and psoas major: anatomic study with application to avoiding iatrogenic injuries - Iwanaga, Joe; Warner, Tyler; Scullen, Tyler A.; von Glinski, Alex; Ishak, Basem; Bui, C. J.; Dumont, Aaron S.; Tubbs, R. Shane (World neurosurgery, 2020)
Background - The proximal course of the obturator nerve as related to the psoas major has been described differently among various authors. Because this relationship is important for better understanding of clinical presentations and during surgical approaches, this study aimed to elucidate this anatomy via cadaveric dissection. - Methods - Twenty obturator nerves from 10 white cadaveric specimens underwent dissection. Observations were made of the relationship between the nerve and psoas major muscle. - Results - On all sides, the obturator nerve descended posterior to the psoas major and never through it. - Conclusions - These results might be important to clinicians who interpret radiology of this region, to clinicians who treat patients with presumed obturator compression syndromes, or to surgeons who operate near the intracavitary part of the obturator nerve.